Numerical Simulation of Supraglacial Debris Mobility: Implications for Ablation and Landform Genesis - Moore, Peter L. (Frontiers in Earth Science, 2021)
Supraglacial debris does not remain fixed atop ablating ice, but can move across the ice surface as supraglacial topography evolves. This active debris movement (distinct from passive movement due to underlying ice motion) affects landform genesis as well as the rate and spatial distribution of ablation. While observations of debris transport across evolving supraglacial topography are abundant, models of these coupled processes over timescales of decades and longer are few. Here I adapt a numerical model of coupled ablation and active debris transport to simulate the evolution of an idealized debris-covered glacier on the timescale of complete de-icing. The model includes ablation that depends on supraglacial debris thickness and a hillslope-scale debris transport function that scales non-linearly with slope angle. Ice thickness and debris distribution evolve with model time, allowing complete simulation of de-icing and landform construction in an idealized glacier test-section. The model produces supraglacial relief that leads to topographic inversions consistent with conceptual models of hummocky landform genesis. Model results indicate that the relief of the glacier surface and postglacial hummocks depend on the relationship between characteristic timescales for ablation and debris transport. When the characteristic transport timescale is comparatively small, topographic inversions are rapid and supraglacial and postglacial relief is subdued. In contrast, when the ablation timescale is comparatively small but debris still mobile, fewer, more pronounced inversions occur and relief is larger. An intermediate case between these end-members appears to optimize both postglacial relief and the rate of de-icing compared with immobile debris. This enhancement of de-icing due to debris mobility could contribute to the observed anomalous rates of ablation in some debris-covered glaciers.